Inhibition of SARS-CoV-2 polymerase by nucleotide analogs: a single molecule perspective - Seifert, Mona (bioRxiv, 2021)
The nucleotide analog Remdesivir (RDV) is the only FDA-approved antiviral therapy to treat infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The physical basis for efficient utilization of RDV by SARS-CoV-2 polymerase is unknown. Here, we characterize the impact of RDV and other nucleotide analogs on RNA synthesis by the polymerase using a high-throughput, single-molecule, magnetic-tweezers platform. The location of the modification in the ribose or in the base dictates the catalytic pathway(s) used for its incorporation. We reveal that RDV incorporation does not terminate viral RNA synthesis, but leads the polymerase into deep backtrack, which may appear as termination in traditional ensemble assays. SARS-CoV-2 is able to evade the endogenously synthesized product of the viperin antiviral protein, ddhCTP, though the polymerase incorporates this nucleotide analog well. This experimental paradigm is essential to the discovery and development of therapeutics targeting viral polymerases.